Glutathione carbon dots as an intracellular reactive oxygen species scavenger for reducing cisplatin‐induced ototoxicity - Yaqin Tu; Guorun Fan; Nan Wu; Bo Liu; Haiying Sun; Qiong Wang; Wenqing Zou; Hongjun Xiao; Songwei Tan (View, 2024)
Abstract It is widely recognized that platinum‐based chemotherapy, particularly cisplatin therapy, can cause ototoxicity. At present, there are no Food and Drug Administration‐approved drugs to prevent or alleviate ototoxicity. Ototoxicity is generally believed to be caused by excessive reactive oxygen species production in the inner ear. Accordingly, a variety of antioxidants have been developed to protect against ototoxicity. To improve the efficiency of drug delivery to the cochlea, here, we synthesized simple and easy‐to‐obtain glutathione carbon dots (GSH CDs) with ultra‐small dimensions. The experimental results revealed that the GSH CDs have strong free‐radical scavenging activity and can restore mitochondrial function, maintain hair cell stability, and protect hair cells from cisplatin‐induced oxidative stress. Thus, GSH CDs may serve as a new therapeutic agent for preventing cisplatin‐induced ototoxicity.